(3HTQi GddHjH HPcQ GdMHjHs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s ((3CMeO Hf YHO GdYRjR Hf YHO GdcQje Hf CHj WGdH Hf Ydi Hf YHO Gddg Hf SjOge ddNejfi s)
(3ChdgG (B:s
(3HYO MeO Gddg Ydi Lejd GdBdGA adeG QhjJ bUjOI cYH Hf RgjQ (B((3HGfJ SYGO(B) (3jeOM HgG SjO GdeQSdjf BKQJ GdJHQc HgPG GdSdhc Ke hLOJ HYO Pdc ef CSeGFg Ydjg GdSdGe afXeJ bUjOg ajgG s
(3BNQgG (B:s
(3PcQ CMGOjK JJYdb HGdeMHI ai Gddg , heMHI Gddg JYGdi , heMHI QShdg Udi Gddg Ydjg hSde eG QCjJ ef GdfGS CMeOi(B[(3jMH(B] (3eMH CUMGH eMemO eMeO Udi Gddg Ydjg hSde BNQg hGdMeO ddg s
(3fSNI QGHYIs
(3HBNQgG bQGAI CMeO Hf YHO GdMb dgPG GdcJGH Ydi hGdOg TjN GdESdGes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
Keywords: (3GdCOHs